2007
DOI: 10.1128/jb.00554-07
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Exclusion Mechanism for Carbon Resource Partitioning in Aggregatibacter actinomycetemcomitans

Abstract: The bacterium Aggregatibacter actinomycetemcomitans is a common commensal of the human oral cavity and the putative causative agent of the disease localized aggressive periodontitis. A. actinomycetemcomitans is a slow-growing bacterium that possesses limited metabolic machinery for carbon utilization. This likely impacts its ability to colonize the oral cavity, where growth and community composition is mediated by carbon availability. We present evidence that in the presence of the in vivo relevant carbon subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
117
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 50 publications
2
117
0
3
Order By: Relevance
“…A. actinomycetemcomitans strains VT1169 (44), Y4 (45), S. strain Challis DL1.1 (ATCC 49818), E. coli DH5␣, and E. coli SM10 were used in this study. A. actinomycetemcomitans strains were grown in brain heart infusion medium, tryptic soy broth ϩ 0.5% yeast extract (TSBYE), or chemically defined medium (CDM) with 20 mM glucose (15). Culture conditions were at 37°C in a 10% (vol/vol) CO 2 atmosphere with shaking at 165 rpm unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A. actinomycetemcomitans strains VT1169 (44), Y4 (45), S. strain Challis DL1.1 (ATCC 49818), E. coli DH5␣, and E. coli SM10 were used in this study. A. actinomycetemcomitans strains were grown in brain heart infusion medium, tryptic soy broth ϩ 0.5% yeast extract (TSBYE), or chemically defined medium (CDM) with 20 mM glucose (15). Culture conditions were at 37°C in a 10% (vol/vol) CO 2 atmosphere with shaking at 165 rpm unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, previous studies demonstrated that A. actinomycetemcomitans preferentially utilizes lactic acid over high-energy carbon sources, such as glucose, despite the fact that this bacterium grows significantly more slowly with lactic acid (15). The ability to preferentially use lactic acid not only eliminates caries-causing lactic acid from the oral environment but eliminates the need for A. actinomycetemcomitans to compete with the more numerous and rapidly growing oral streptococci for carbon (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent work has demonstrated that in vitro Sg can grow in coculture with the opportunistic oral pathogen Aggregatibacter actinomycetemcomitans (Aa) (4). In co-culture Aa preferentially utilizes Sg-produced lactic acid (5) and detoxifies Sg-produced hydrogen peroxide using the KatA enzyme (6). Recent work has demonstrated that hydrogen peroxide induces katA expression as well as apiA, which encodes an immunoprotective factor that renders Aa more resistant to killing by host innate immunity (5).…”
mentioning
confidence: 99%
“…In co-culture Aa preferentially utilizes Sg-produced lactic acid (5) and detoxifies Sg-produced hydrogen peroxide using the KatA enzyme (6). Recent work has demonstrated that hydrogen peroxide induces katA expression as well as apiA, which encodes an immunoprotective factor that renders Aa more resistant to killing by host innate immunity (5). These studies demonstrated induction of gene expression in mixed species biofilms by Sg-produced hydrogen peroxide.…”
mentioning
confidence: 99%